2015
DOI: 10.1186/s12888-015-0658-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying and predicting depression literacy of undergraduates: a cross sectional study in Sri Lanka

Abstract: BackgroundThe high rates of depression and low rates of related help-seeking among undergraduates are matters for concern. In response to the need to examine their knowledge about depression and its management, and the dearth of such research from non-western developing countries, this study examined the depression literacy of undergraduates in Sri Lanka.MethodsA questionnaire was administered among 4671 undergraduates to examine their depression literacy relating to problem-recognition, measured using a vigne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 45 publications
8
20
0
Order By: Relevance
“…Logistic regression in this study expressed that female gender, age increasing, and higher education significantly increased the likelihood of a correct depression diagnosis, which was similar to that found by Amarasuriya in Sri Lanka,[19] Reavley[12] in Australia and Furnham[20] in the United Kingdom. However, the finding on gender contradicted with results of Sayarifard[10] and Yeap[21] studies in Iran and Malaysia, respectively.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Logistic regression in this study expressed that female gender, age increasing, and higher education significantly increased the likelihood of a correct depression diagnosis, which was similar to that found by Amarasuriya in Sri Lanka,[19] Reavley[12] in Australia and Furnham[20] in the United Kingdom. However, the finding on gender contradicted with results of Sayarifard[10] and Yeap[21] studies in Iran and Malaysia, respectively.…”
Section: Discussionsupporting
confidence: 81%
“…The present study showed that the ability to recognize the disorder in Tehran city (53%) and the suburb (30%) was both low, which was consistent with the findings of the Sayarifard's study among Tehran University of Medical Sciences students, where less than 40% of students were able to correctly diagnose depression. [10] This finding was very low in comparison with the 70% achieved in a number of countries, including the Reavley's study[12] in Australian students and the Marie's study[14] in the New Zealand community, but more similar to the results of the Jorm,[17] Olsson,[18] and Amarasuriya[19] studies in Japan, America, and Sri Lanka.…”
Section: Discussionmentioning
confidence: 80%
“…Mental illness among medical students has often been swept under the carpet and under-recognized [34], though the rates of these mental illness among this vulnerable population are by no means trivial. A recent meta-analysis of depression among medical students concluded that the global prevalence was around 28% [1].…”
Section: Discussionmentioning
confidence: 99%
“…As expected, fourth-year and fifth-year medical students were significantly more likely to correctly recognise the disorder described in the vignette compared with students in their first year of medicine, a finding which concurs with previous research. 13 Medical school curricula for first-year students only include very limited and preliminary information relating to psychiatry, where the majority of psychiatric teaching clerkship and placements occurs in the latter years of the course. Therefore, it is not surprising that the knowledge and ability to correctly recognise signs and symptoms of various disorders among first-year students is poorer than students in their final years of medicine.…”
Section: Discussionmentioning
confidence: 99%
“…While very few studies have explored mental health literacy solely among medical students, studies have investigated this concept among university and college students. Findings have revealed that in comparison medical students could better recognise mental illnesses 13 or had better mental health literacy than students studying within other disciplines. 14 15 Despite this, medical students report feeling underprepared to manage mental health problems.…”
Section: Introductionmentioning
confidence: 99%